Time-resolved luminescence detection of peroxynitrite using a reactivity-based lanthanide probe. Issue 12 (25th February 2020) - Breen, Colum; Pal, Robert; Elsegood, Mark R. J.; Teat, Simon J.; Iza, Felipe; Wende, Kristian; Buckley, Benjamin R.; Butler, Stephen J.
Abstract : Reactivity-based europium(iii ) probe displays excellent selectivity for peroxynitrite (ONOO − ), enabling its time-resolved luminescence detection in living cells. Abstract : Peroxynitrite (ONOO − ) is a powerful and short-lived oxidant formed in vivo, which can react with most biomolecules directly. To fully understand the roles of ONOO − in cell biology, improved methods for the selective detection and real-time analysis of ONOO − are needed. We present a water-soluble, luminescent europium(iii ) probe for the rapid and sensitive detection of peroxynitrite in human serum, living cells and biological matrices. We have utilised the long luminescence lifetime of the probe to measure ONOO − in a time-resolved manner, effectively avoiding the influence of autofluorescence in biological samples. To demonstrate the utility of the Eu(iii ) probe, we monitored the production of ONOO − in different cell lines, following treatment with a cold atmospheric plasma device commonly used in the clinic for skin wound treatment.